2022
DOI: 10.3390/land11060920
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Evolution Characteristics and Its Driving Mechanism of Land Use/Cover in Vietnam from 2000 to 2020

Abstract: Research on the spatial distribution and dynamic evolution of land use/land cover (LULC) is the basis for land management and ecological protection. However, there is currently a lack of long-term analysis on the evolution of LULC on the national scale in Vietnam. Based on the GLC_FCS30 dataset, this paper analyzed the temporal and spatial evolution of LULC in Vietnam from 2000 to 2020 as well as its driving mechanism using methods such as dynamicity, flow direction diagrams, principal component analysis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Studies on LULC changes in Vietnam, Cambodia, and Laos also found that national economic development and human activities have a greater impact on LUCC in these countries. Among the factors that have a more pronounced impact are GDP, population, and urbanization rates [42,43,45]. Our research also shows that at the national scale, socio-economic and agricultural development have a greater impact on LUCC in Myanmar.…”
Section: Lucc and Its Influencing Factorssupporting
confidence: 50%
“…Studies on LULC changes in Vietnam, Cambodia, and Laos also found that national economic development and human activities have a greater impact on LUCC in these countries. Among the factors that have a more pronounced impact are GDP, population, and urbanization rates [42,43,45]. Our research also shows that at the national scale, socio-economic and agricultural development have a greater impact on LUCC in Myanmar.…”
Section: Lucc and Its Influencing Factorssupporting
confidence: 50%
“…There are several factors contributing to the expansion of builtup areas, with the main factors being population growth, urbanization, and urban planning policies [Waiyasusri, 2021;Singh et al, 2022]. The population growth during this period has led to an increasing demand for housing, driving the expansion and development of urban areas and residential areas in Ha Nam province [Niu et al, 2022]. Additionally, the process of urbanization and the expansion of urban areas have resulted in the development of new urban areas, the renovation and expansion of urban infrastructure, and the construction of urban areas outside existing urban centers [Wang et al, 2021].…”
Section: Land Use/land Cover Changementioning
confidence: 99%
“…Biazin et al [31] found that drought vulnerability is intimately linked to land use type and social background through remote sensing technology, drought vulnerability analysis and field observation, and social context. Niu et al [32] used principal component analysis and multivariate stepwise regression to analyze LUCC in Vietnam. They showed that LUCC in Vietnam is affected by economic development, population, and urbanization rate.…”
Section: Introductionmentioning
confidence: 99%